PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI PENGGUNAAN MODEL SOBRY PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS IV SDN 31 AMPENAN TAHUN PELAJARAN 2022/2023 - Rina Wardaniati (Al-mujahidah, 2023)
This research aims to know the increased for students learning motivation through the use of the SOBRY model on PAI subjects in Grade IV SDN 31 Ampenan. This type of research is classroom action research (CAR) which uses two cycles, each cycle consists of planning, action, observation and reflection stages. The subjects of this research were grade IVA at SDN 31 Ampenan with 31 students. The instruments used in this research are observation, documentation and questionnaires. The data collection technique in this research used teacher and student observation sheets. The data analysis technique uses qualitative descriptive data analysis. The research results show that the use of the SOBRY model (Convey, Organize, Ask, Celebrate, Convince) can increase the learning motivation of grade IV students at SDN 31 Ampenan. This can be seen from the completeness of the percentage of student learning motivation from cycle I to cycle II. The average student learning motivation in cycle I was 50.8%, increasing by 36.8% in cycle II with an average of 87.6%.